2020
DOI: 10.1002/smll.202001772
|View full text |Cite
|
Sign up to set email alerts
|

Dual Passivation of CsPbI3 Perovskite Nanocrystals with Amino Acid Ligands for Efficient Quantum Dot Solar Cells

Abstract: Inorganic CsPbI3 perovskite quantum dot (PQD) receives increasing attention for the application in the new generation solar cells, but the defects on the surface of PQDs significantly affect the photovoltaic performance and stability of solar cells. Herein, the amino acids are used as dual‐passivation ligands to passivate the surface defects of CsPbI3 PQDs using a facile single‐step ligand exchange strategy. The PQD surface properties are investigated in depth by combining experimental studies and theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
144
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(162 citation statements)
references
References 71 publications
6
144
1
2
Order By: Relevance
“…The IPCE characterization relates also to many factors such as the band gap of the photoactive material [ 32 , 33 , 34 ], the light that goes through the transparent electrodes and the effectiveness of charge collection at certain wavelength [ 32 , 35 ]. The shape of the IPCE spectra is consistent with previous work, reporting direct planar solar cells architecture, where the onset at short wavelengths is related to light absorbance from the ITO glass and SnO 2 [ 18 ] and the one at the long wavelengths is at 680 nm, below the onset around 700 nm of solar cells employing bulk CsPbI 3 . This demonstrates the preservation of the quantum confinement for both non-treated and UV treated devices [ 4 , 15 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The IPCE characterization relates also to many factors such as the band gap of the photoactive material [ 32 , 33 , 34 ], the light that goes through the transparent electrodes and the effectiveness of charge collection at certain wavelength [ 32 , 35 ]. The shape of the IPCE spectra is consistent with previous work, reporting direct planar solar cells architecture, where the onset at short wavelengths is related to light absorbance from the ITO glass and SnO 2 [ 18 ] and the one at the long wavelengths is at 680 nm, below the onset around 700 nm of solar cells employing bulk CsPbI 3 . This demonstrates the preservation of the quantum confinement for both non-treated and UV treated devices [ 4 , 15 , 36 , 37 ].…”
Section: Resultssupporting
confidence: 89%
“…At the same time, this approach is difficult to replicate in planar solar cells, since the mesoporous titania is more prone to the infiltration of the chemicals and salts used in this strategy. In planar solar cells architecture, the efficiency exceeded over 14%, with a stability of almost 10 days if the QDs are passivated with a treatment with glycine [18]. Therefore, there is a lack of strategies that limit the use of chemicals and solvents to improve the CsPbI 3 stability, preserving the efficiency and making it easy to reproduce regardless of the structure used.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the addition of amino acids during MAPbBr3 synthesis was shown to passivate the crystal surface, facilitating the formation of nanocrystals thereby improving devices performence. [92,93] In our study, we showed that not only do the amino acids passivate the MAPbBr3 crystal surface, but they also become incorporated into its lattice, thus, alter the optical and thermal properties of the perovskite. Another cardinal outcome of the incoporation is the finding that it enhances the stability of the host MAPbBr3 crystal under humid conditions.…”
Section: Resultsmentioning
confidence: 71%
“…The CsPbBr 3 ‐OA/OAm NCs were prepared through a traditional hot‐injection method as reported in the literature; [33] the details of the synthesis are described in the Supporting Information. The as‐prepared CsPbBr 3 ‐OA/OAm NCs were added to glycine‐saturated ethyl acetate solution to generate CsPbBr 3 ‐Glycine NCs through a facile ligand‐exchange approach [34] (Scheme S1, Supporting Information); the detailed procedures are presented in the Supporting Information. The effectiveness of ligand exchange was investigated by Fourier transform infrared (FTIR) spectroscopy measurements.…”
Section: Figurementioning
confidence: 99%